OxLDL-mediated cellular senescence is associated with increased NADPH oxidase p47phox recruitment to caveolae. Issue 3 (12th June 2018) - Wang, Jing; Bai, Yuzhi; Zhao, Xia; Ru, Jing; Kang, Ning; Tian, Tian; Tang, Liying; An, Yun; Li, Pei
Abstract : Atherosclerosis develops as a consequence of inflammation and cell senescence. In critical factors involved in the atherosclerotic changes, reactive oxygen species (ROS) generation is considered a leading cause. While NADPH oxidases, particularly NOX2, are the main sources of ROS, how they are regulated in the disease is incompletely understood. In addition, how caveolae, the membrane structure implicated in oxLDL deposition under vascular endothelia, is involved in the oxLDL-mediated ROS production remains mostly elusive. We report here that macrophages exposed to oxLDL up-regulate its caveolin-1 expression, and the latter in turn up-regulates NOX2 p47phox level. This combination effect results in increased cellular senescence. Interestingly, oxLDL treatment causes the p47phox residing in the cytosol to translocate to the caveolae. Immunoprecipitation assays confirms that cavelin-1 is in high degree association with p47phox. These results suggest caveolin-1 may serve as the membrane target for p47phox and as a switch for ROS production following oxLDL exposure. Our results reveal a previously unknown molecular event in oxLDL-mediated cellular ageing, and may provide a target for clinical intervention for atherosclerosis.